The politics of child protection: contemporary developments and future directions - Parton, Nigel (Palgrave Macmillan, 2014)
"From Every Child Matters and the Munro Review, to changing shifts in thinking from Coalition government; the child protection system has seen dramatic political and policy developments over recent years. This book brings you a critical analysis of these developments from a leading writer and commentator. It begins by exploring the origins of present-day arrangements, locating English policy and practice in both a wider British and international context. It examines tragic cases such as 'Baby P' and Maria Colwell, considering their impact on public and professional attitudes and, in turn, the implications for the child protection system. Looking to the future of child protection, Nigel Parton considers the current state of the system and argues that we need to address wider social and political issues, including poverty, class and inequality. Original, authoritative and up-to-date, The Politics of Child Protection is an important book for all students, practitioners and researchers interested in safeguarding and child protection. "--